High Level Secretion of Laccase (LccH) from a Newly Isolated White-Rot Basidiomycete, Hexagonia hirta MSF2 - Kandasamy, Sujatha; Muniraj, Iniya K.; Purushothaman, Namitha; Sekar, Ashika; Sharmila, D. J. S.; Kumarasamy, Ramasamy; Uthandi, Sivakumar (Frontiers in Microbiology, 2016)
Newer and novel laccases attract considerable attention due to its promising and valuable multiple applications in biotech industry. This present investigation documents, for the first time, on high level extracellular secretion of laccase (LccH) in newly isolated wood-degrading basidiomycete Hexagonia hirta MSF2. LccH was optimally active at 40°C in citrate phosphate buffer with a pH of 3.4. Optimized Cu2+ in glucose yeast extract (GY) medium enhanced the LccH production by H. hirta to 1944.44 U.ml-1. A further increment in LccH activity of 5671.30 U.ml-1 was achieved by the addition of a phenolic inducer, 2,5 Xylidine. Zymogram and sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS–PAGE) analysis of LccH revealed that LccH is a monomer with a molecular mass of 66 kDa. MALDI-TOF-MS based peptide mass fingerprinting and comparative modelling of the amino acid sequence of LccH showed that it was closer to Trametes sp. AH28-2 (PDB: 3KW7) with 48% identity, 95% coverage, 0.011 alignment score and RMSD of 0.497Å. Crude LccH delignified lignocellulosic biomass such as wood and corncob, to a level of 28.6 and 16.5 % respectively. Such high level secretion, thermal and solvent stability of LccH make H.hirta a potential candidate not only for LccH production and biodelignification but also generation of lignin derived aromatic feed stock chemicals for industrial and environmental applications.